AB0362 Serum Lipid Level Changes Associated with Tocilizumab Treatment: Our Experience in Two University Hospitals. (15th July 2016) - García-Núñez, B.; Lόpez-Salguero, S.; Sivera, F.; Andrés, M.
Abstract : Background: Tocilizumab (TCZ) is a humanised monoclonal antibody against the Interleukin-6 (IL-6) receptor effective in patients with rheumatoid arthritis (RA) with an inadequate response to conventional DMARDs or an anti-TNF biologic. Among its side effects, a change in the serum lipid profile due to an increase of low density lipoproteins (LDLc) and of high density lipoproteins (HDLc) has been previously described. Its impact and proper management is still uncertain. Objectives: To analyze the changes in serum lipid levels in patients under TCZ treatment. Methods: Retrospective review. Patients treated with TCZ and complete serum lipid profile (total cholesterol, LDLc, HDLc, triglycerides) in two different rheumatology units were selected. Three time-points were established: 1) baseline; 2) one month after the start of TCZ; 3) six monthts after the start of TCZ. Epidemiologic and clinical data on al patients and laboratory findings (C reactive protein – CRP, erythrocyte sedimentation rate – ESR) at the given time-points were also recorded. A before-after comparative anlaysis using Wilcoxon's test, an a correlational analysis with inflammation laboratory parameters using Spearman's Rho test were performed. Results: Thirty-five patients were included: 34 patients with rheumatoid arthritis and one with idiopathic retroperitoneal fibrosis. Patients were a mean (p25–75) of 57.5 years (51.8–63.3) old, and 30 (86%) were women. Table 1 shows the variations in lipid parameters at the different timepoints. A mild increase in HDLc levels was observed after one month of treatment which was maintained at 6 months later, but with no statistical significance (p=0.36). A significant elevation was observed in the remaining lipid paramenters (total cholesterol, LDLc, triglycerides) after one month of treatment, which dissapeared after 6 months of treatment. Inflammatory markers decreased significantly and persistently after the beginnig of TCZ treatment. In the correlation analysis no association was found between lipid levels and inflammatory markers (p>0.05 for all comparisons). Conclusions: With TCZ, most lipid parameters show a significant but transitory increase. A mild though non-significant increase in HDLc levels was also observed. The antiatherogenic benefit of TCZ might be mediated by qualitative changes in the HDLc molecule. Prospective and larger studies are needed to characterize these results better. Disclosure of Interest: None declared